Advanced and functionalized biomass-derived carbon materials for energy conversion, storage, and smart systems: Synthesis strategies, structure–property relationships, and AI integration - Basiru O. Yusuf; Mansur Aliyu; Ijaz Hussain; Mustapha Umar; Aliyu M. Alhassan; Yahuza Nantomah Abdulai; Jamilu Nura Musa; Esraa Kotob; Omer A. Taialla; Ismail Abdulazeez; Saheed A. Ganiyu (Biomass and Bioenergy, 2027)

Minimalistic Design and Nanoformulation of Pyrazolone and Imidazolone Analogs as Potent FabF (KAS II) Inhibitors for Combating Pseudomonas Aeruginosa Infection - Mohammed Almaghrabi; Shaimaa Hussein; Safaa A. Turkistani; Arafa Musa; Raed Alghamdi; Tawfiq N. Juraybi; Magdi E. A. Zaki; Waad A. Samman; Sobhi M. Gomha; Saeed M. Tayeb; Mohammed S. Abdulrahman; Hany E. A. Ahmed (Journal of Pharmaceutical Innovation, 2026)

Geochemical fractionation, mineralogical insights and environmental risk of toxic elements in mining-impacted soils of Zamfara State, Nigeria - Jajati Mandal; Waheed Ariyo Bakare; Effiom Oku; Barnabas Iliya Musa; Abhishek Sharma; A.S.M. Fazle Bari; Michael D. Wood; Simon M. Hutchinson; Debapriya Mondal; Mohammad Mahmudur Rahman (Applied Geochemistry, 2026)

Plasmo3Net: A convolutional neural network-based algorithm for detecting malaria parasites in thin blood smear images - Afolabi Owoloye; Funmilayo C. Ligali; Ojochenemi A. Enejoh; Oluwafemi Agosile; Adesola Z. Musa; Oluwagbemiga Aina; Adetunji P. Adewole; Emmanuel T. Idowu; Kolapo M. Oyebola (Next Research, 2026)

Knowledge Without Confidence: Internal Medicine Residents’ Preparedness for Oncologic Emergencies and Goals-of-Care Communication - Musa Kiyani; Daniel M. Lichtstein (Journal of Cancer Education, 2026)

Salinity tolerance in blood cockles environmental conditions associated with the presence of Tegillarca granosa and its salinity tolerance: field observations and laboratory experiments - H. Muhd-Farouk; K. K. K. Yaacob; N. Hanafi; M. A. Hamid; M. N. Azra; A. Amin-Safwan; N. Musa; A. Hidir; H. Ma; M. Ikhwanuddin (Molluscan Research, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Molecular epidemiology and genetic profiling of Anaplasma ovis, Bartonella sp., and Toxoplasma gondii in domestic cats - Fakiha Tur Rehman; Uzair Ahmad; Rakshanda Sardar; Musa Rahman; Hira Muqaddas; Esmael M. Alyami; Ohoud A. Alghamdi; Gehan M. Elossaily; Shakir Ullah; Asmat Ullah Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Prevalence of Hepatitis B virus Genotypes and their Correlation with Serological Markers among Chronic Infected Patients in Sudan - Ghanim Eltahir Ahmed Yousif; Mohammed AW. Almorish; Hassan Hussein Musa; Ahmed M. E. Elkhalifa; Rasha M. Mahrous; Naser Eldin Bilal (Current Microbiology, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrating mosquito behavior and transfusion risk for evidence-based malaria policy: a case study of three South Sudan provinces - Nneka Iheonu; Musa Rabiu; Folashade M. Jimoh; Anne O. Atede; Victoria I. Okeowo; Abdulrahaman L. Suleiman (Modeling Earth Systems and Environment, 2026)
Malaria is a major public health burden in South Sudan, one of the most malaria-endemic countries worldwide. In 2020, approximately 2.3 million cases and 4,500 deaths were reported. This study developed and analyzed a deterministic malaria transmission model incorporating transfusion-mediated infections and distinct diurnal and nocturnal mosquito biting rates. Using surveillance data from Central Equatoria State (CES), Warrap (WRP), and Western Bahr el Ghazal (WBGZ), Bayesian inference estimated key transmission parameters. Posterior results showed nocturnal biting dominance in WRP and WBGZ, while CES had balanced day-night exposure, with reproduction number $$\mathcal {R}_0$$ ranging from 2.81 in CES to 5.61 in WBGZ. Model calibration reproduced weekly incidence, capturing peak intensities and inter-epidemic troughs. Simulations indicated that increasing either day- or night-biting independently amplifies infections, but combined increases produce synergistic growth in exposed and infectious populations. Treatment delays disproportionately increased infectious populations in high-transmission CES. Sensitivity analysis identified transmission probabilities and mosquito biting parameters as most influential, with CES more sensitive to daytime biting and WRP/WBGZ to nighttime biting. Optimal control simulations showed that combining bed-net/repellent use ( $$u_1$$ ) with parasite clearance in donated blood ( $$u_3$$ ) rapidly reduced infections. Cost-effectiveness analysis confirmed Strategy VI ( $$u_1 + u_3$$ ) as the most efficient, averting 1,925,821 cases at $110 (ICER $$≈ 5.712 × 10^{-5}$$ ). Results emphasize spatially adaptive strategies: integrated day-night vector control and transfusion safety in CES, nocturnal vector suppression in WRP and WBGZ, and prompt treatment across all provinces. The study provides actionable, evidence-based guidance linking epidemiological mechanisms to cost-effective policy interventions.

Identifying Optimal Drug Loading in Stable Amorphous Solid Dispersion Formulations: A Rheological Approach - Sagar Narala; Fengyuan Yang; Kapish Karan; Michael Kogan; Ian Pierce; Osama M. Musa (AAPS PharmSciTech, 2026)

Holistic model validation and interpretation with SHAP for machine learning models: predicting compressive strength of fly ash geopolymer concrete using optimization algorithms and ensemble model - Mahmud M. Jibril; Salim Idris Malami; Sani Isa Abba; Musa Adamu; Yasser E. Ibrahim; Mukhtar Fatihu Hamza (Innovative Infrastructure Solutions, 2026)

Cell-based and computational toxicity profiling of thiourea and imine derivatives in Acanthamoeba sp. as environmental bioindicators for potential optoelectronic applications - Thivyan Manisekaran; Wan M. Khairul; Nur Amirah Nabilah Mohd Rashid; Fariq Zulfaqar Musa; Syed Ahmad Tajudin Tuan Johari; Siti Aisyah Razali; Fatimah Hashim; Mas Mohammed; Rafizah Rahamathullah; Amira Nabiha Najwa Syahrul Fahmy (Chemosphere, 2026)

Numerical simulation of breakdown threshold voltage in charging coils of wireless power transfer systems - Umar Musa; Abdullahi Abubakar Mas’ud; Johnatan M. Rodríguez-Serna; Abdullahi Mohammad; Muhammad Lotfi Hussain; Firdaus Muhammad-Sukki (Next Research, 2026)

Carcinogenic risk assessment, hydrogeochemical signatures, and irrigation suitability of groundwater within Ajaokuta and environs, North Central, Nigeria - K. O. Musa; F. A. Akpah; O. C. Akakuru; G. O. Aigbadon; A. C. Nanfa; M. M. Shaibu; J. B. Jimoh (International Journal of Energy and Water Resources, 2026)

Laportea aestuans (L.) Chew leaves extract ameliorates hyperglycaemia-mediated oxido-inflammatory stress in high-fat diet/streptozotocin-induced diabetes in rats - Shaza Ibrahim Musa; Abiodun A. Adeyemi; Abayomi M. Ajayi (Advances in Traditional Medicine, 2026)

First record of microplastics found in shark mermaid’s purses: a hidden threat to ocean apex predators during embryonic stage - Syafiq M. Musa; Nabila N. Nasharuddin; Azwan Mat Lazim; Yar Johan; Mazlan Abd. Ghaffar; Diana A.Z. Abidin (Marine Biology Research, 2026)

An approximate approach for quantifying the effects of deep well excavation on nearby masonry buildings - Abubakr E. S. Musa; Madyan A. Al-Shugaa; Yassir M. H. Mustafa; Amin Al-Fakih; Mohammed A. Al-Osta (Innovative Infrastructure Solutions, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Anti-inflammatory effect of pirfenidone compared to dexamethasone in ulcerative colitis model induced by acetic acid in rats: involvement of miR-146a and TLR4/NF-κB signaling - Hanaa Wanas; Dina M. Mekawy; Reham M. Raafat Hamed; Ragaey Ahmad Eid; Eman A. Abd Elmaogod; Eid N. Ali Musa; Mohamed A. M. Allam; Abdelrahman M. Attia; Amr M. Galal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Bangko plant (Rhizophora mucronata) as a nature-based solution for coastal toxic metal pollution - M. Al Mustawa; P. Taba; B. Musa; R. Mardiyanti (International Journal of Environmental Science and Technology, 2026)

Artificial Intelligence in Sustainable Drainage Water Reuse: A Comprehensive Review - Layth Saeed Abdulameer; Mushtaq K. Abdalrahem; Najah M. L. Al Maimuri; Ahmed N. Al-Dujaili; Musa Al-Shammari (Water Conservation Science and Engineering, 2025)

Integrating machine learning and environmental-soil variables for estimating soluble and exchangeable potassium in dryland regions: agronomical implications - Musaab Musa; Mohammed A. Elsheikh; Magboul M. S. Siddig; Mohammed M. Omar; Fuat Kaya; Eric C. Brevik (Plant and Soil, 2025)

Innovative resource recovery: converting discarded disposable diapers (D3) into activated carbon using Box–Behnken design - D. R. S. I. Shah; N. F. Anuar; S. Z. Roslan; M. Musa; W. M. A. W. Daud; A. B. Alias; N. Aghamohammadi (International Journal of Environmental Science and Technology, 2025)
This study aims to optimize the production of activated carbon from discarded disposable diapers (D3AC) using Box–Behnken design (BBD) under response surface methodology. Biochar (D3B) was initially produced via carbonization at 900 °C for 90 min under nitrogen flow, followed by physical activation with CO 2 . The BBD model demonstrated strong reliability (R 2 = 0.9972), effectively predicting the influence of activation temperature, holding time, and CO₂ flowrate on surface area development. Under optimized conditions, D3AC exhibited a BET surface area of 1235.32 m 2 /g, significantly higher than that of D3B (479.79 m 2 /g), with a well-developed microporous structure. In contrast, D3B displayed higher total pore volume and ash content. These findings confirm the successful enhancement of porosity and surface characteristics through parameter optimization and support the feasibility of thermochemical conversion using statistical design. Graphical abstract

Nutrient Buffering and Redox Dynamics at Plug and Pond Restoration Sites in the Valles Caldera National Preserve, New Mexico, USA - Brent D. Newman; Jeffrey M. Heikoop; Dea Musa; Rick Kelley; Elaine Jacobs; Rose Adams; Steve Vrooman; Kina Murphy; Wetherbee Dorshow (Wetlands, 2025)

GC-MS and HPLC-FLD for sensitive assay of toxic cyclohexylamine in artificial sweetener tablets and human biological fluids - Hazim M. Ali; Amr A. Essawy; Ahmed Hamad Alanazi; Arafa Musa; Ahmed Emad F. Abbas; Ibrahim Bayoumi Abdel-Farid; Mohammed Gamal (Food and Chemical Toxicology, 2025)

Development of novel iron and copper-loaded mesoporous silica particles with exceptional visible-light-induced photocatalytic properties for ultra-fast removal of organic pollutants from wastewater - Aatif Ijaz; Kubilay Sahin; Musa Dirak; M. Baris Yagci; Safacan Kolemen; A. Levent Demirel; Annamaria Miko (Journal of Water Process Engineering, 2025)

Multi-target anti-inflammatory and cytotoxic activities of flavonoids from Varthemia iphionoides Boiss. & C. I. Blanche - Amal Al-Aboudi; Musa Abu Zarga; Wafa Hourani; Aisha Al-Rahmoni; Almas Jabeen; M. Iqbal Choudhary (Natural Product Research, 2025)

Ferulic Acid Ameliorates Chromium-Induced Nephrotoxicity: Modulation of PERK/eIF2α/ATF4/CHOP, Nrf2, and Inflammatory Signaling - Samyah T. Alanazi; Samir A. Salama; Musaad M. Althobaiti; Abdullah M. Almalki; Afnan Bakhsh; Arafa Musa; Alaa A. Mohammed (Biological Trace Element Research, 2025)

Theaflavin alleviates cisplatin-induced nephrotoxicity: Targeting SIRT1/p53/FOXO3a/Nrf2 signaling and the NF-kB inflammatory cascade - Samyah T. Alanazi; Samir A. Salama; Musaad M. Althobaiti; Afnan Bakhsh; Najla M. Aljehani; Ebtisam Alanazi; Maha T. Alanazi; Arafa Musa (Food and Chemical Toxicology, 2025)

Artificial Intelligence in Climate-Resilient Water Management: A Systematic Review of Applications, Challenges, and Future Directions - Layth Abdulameer; Mahmoud Saleh Al-Khafaji; Aysar Tuma Al-Awadi; Najah M. L. Al Maimuri; Musa Al-Shammari; Ahmed N. Al-Dujaili; DhiyaAl‑Jumeily (Water Conservation Science and Engineering, 2025)

Empowering cancer prevention with AI: unlocking new frontiers in prediction, diagnosis, and intervention - Marianna-Foteini Dafni; Mohamed Shih; Agnes Zanotto Manoel; Mohamed Yousif Elamin Yousif; Stavroula Spathi; Chorya Harshal; Gaurang Bhatt; Swarali Yatin Chodnekar; Nicholas Stam Chune; Warda Rasool; Tungki Pratama Umar; Dimitrios C. Moustakas; et al. (Cancer Causes & Control, 2025)

Understanding author choices in the current conservation publishing landscape - Natalie Yoh; Mukhlish Jamal Musa Holle; Jasmin Willis; Lauren F. Rudd; Iain M. Fraser; Diogo Veríssimo (Conservation Biology, 2025)
Conservation literature addresses a broad spectrum of interdisciplinary questions and benefits. Conservation science benefits most when a diverse range of authors are represented, particularly those from countries where much conservation work is focused. In other disciplines, it is well known that barriers and biases exist in the academic publishing sphere, which can affect research dissemination and an author's career development. We used a discrete choice experiment to determine how 7 journal attributes affect authors’ choices of where to publish in conservation. We targeted authors directly by contacting authors published in 18 target journals and indirectly via communication channels for conservation organizations. We only included respondents who had previously published in a conservation‐related journal. We used a multinomial logit model and a latent class model to investigate preferences for all respondents and distinct subpopulations. We identified 3 demographic groups across 1038 respondents (older authors from predominantly middle‐income countries, younger authors from predominantly middle‐income countries, and younger authors from high‐income countries) who had published in conservation journals. Each group exhibited different publishing preferences. Only 2 attributes showed a consistent response across groups: cost to publish negatively affected journal choice, including authors in high‐income countries, and authors had a consistent preference for double‐blind review. Authors from middle‐income countries were willing to pay more for society‐owned journals, unlike authors from high‐income countries. Journals with a broad geographical scope that were open access and that had relatively high impact factors were preferred by 2 of the 3 demographic groups. However, journal scope and open access were more important in dictating journal choice than impact factor. Overall, different demographics had different preferences for journals and were limited in their selection based on attributes such as open access policy. However, the scarcity of respondents from low‐income countries (2% of respondents) highlights the pervasive barriers to representation in conservation research. We recommend journals offer double‐blind review, reduce or remove open access fees, investigate options for free editorial support, and better acknowledge the value of local‐scale single‐species studies. Academic societies in particular must reflect on how their journals support conservation and conservation professionals.

Toxic tuna tales: Tracing microplastic pathways in mackerel tuna (Euthynnus affinis), longtail tuna (Thunnus tonggol), and bullet tuna (Auxis rochei) - Syafiq M. Musa; Sinoretha Sining; Adlin I. Arba'in; Maisarah I. Amizuri; Azwan Mat Lazim; Mazlan Abd. Ghaffar (Marine Pollution Bulletin, 2025)

Optimizing encapsulation of garlic and cinnamon essential oils in silver nanoparticles for enhanced antifungal activity against Botrytis cinerea pathogenic disease - Nahla Alsayd Bouqellah; Awatif M. Abdulmajeed; Fawiziah Khalaf Rashed Alharbi; Ehab Mattar; Faisal Al-Sarraj; Ahmed M. Abdulfattah; Mohamed M. Hassan; Alaa Baazeem; Helal F. Al-Harthi; Arafa Musa; Tahani A.Y. Asseri; Mona H. Soliman (Physiological and Molecular Plant Pathology, 2025)

Biomarker signatures in host rocks and their co-occurring fossil plants from northern Scotland - Olumuyiwa T. Akinsanpe; Adebola O. Akinsanpe; Solomon A. Adekola; Oluwaseye P. Oyetade; Waheed G. Akande; Musa B. Usman; Abdulwahab M. Bello; Uzochukwu K. Benjamin; Adeniyi O. Olusanya; Chikezie Emele (Organic Geochemistry, 2025)

Adsorptive Performance of High Surface Area Date Palm Bunch Activated Carbon Towards Methyl Violet and Fuchsin Basic Dyes Removal: Thermochemical Activation And Statistical Optimization - Muna Sarhan Sando; Ahlam M. Farhan; Ahmad Hapiz; Elmira Kashi; Salis A. Musa; Ali H. Jawad (Water, Air, & Soil Pollution, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Carbon recovery in secondary forests: Insights from three West African countries - Paly N. Titenwi; Moses N. Sainge; Usif Kargbo; Richard A.S. Kamara; Alex Musa; Timothy M. Kabba; Bockarie K. Buanie; Andre L. Njouonkou; Edward Aruna; Martin J.P. Sullivan; Ana Leite; Aida Cuni-Sanchez (Forest Ecology and Management, 2025)

Optimizing the fresh and hardened properties of concrete containing bentonite and crumb rubber using response surface methodology - M. Achyutha Kumar Reddy; Yedlapalli Akhila; Veerendrakumar C. Khed; Musa Adamu; Yasser E. Ibrahim; Sowmya Tippa (Sustainable Chemistry and Pharmacy, 2024)

Recent advances and future prospects of MXene-based photocatalysts in environmental remediations - Basiru O. Yusuf; Mustapha Umar; Mansur Aliyu; Aliyu M. Alhassan; Mohammed Mosaad Awad; Omer A. Taialla; AbdulHakam Shafiu Abdullahi; Jamilu Nura Musa; Khalid R. Alhooshani; Saheed A. Ganiyu (Journal of Environmental Chemical Engineering, 2024)

Mineral Reconnaissance Through Scientific Consensus: First National Prospectivity Maps for PGE–Ni–Cu–Cr and Witwatersrand-type Au Deposits in South Africa - Glen T. Nwaila; Steven E. Zhang; Julie E. Bourdeau; Emmanuel John M. Carranza; Stephanie Enslin; Musa S. D. Manzi; Fenitra Andriampenomanana; Yousef Ghorbani (Natural Resources Research, 2024)
We present here the first experimental science (consensus)-based mineral prospectivity mapping (MPM) method and its validation results in the form of national prospectivity maps and datasets for PGE–Ni–Cu–Cr and Witwatersrand-type Au deposits in South Africa. The research objectives were: (1) to develop the method toward applicative uses; (2) to the extent possible, validate the effectiveness of the method; and (3) to provide national MPM products. The MPM method was validated by targeting mega-deposits within the world’s largest and best exploited geological systems and mining districts—the Bushveld Complex and the Witwatersrand Basin. Their incomparable knowledge and mega-deposit status make them the most useful for validating MPM methods, serving as “certified reference targets”. Our MPM method is built using scientific consensus via deep ensemble construction, using workflow experimentation that propagates uncertainty of subjective workflow choices by mimicking the outcome of an ensemble of data scientists. The consensus models are a data-driven equivalent to expert aggregation, increasing confidence in our MPM products. By capturing workflow-induced uncertainty, the study produced MPM products that not only highlight potential exploration targets but also offer a spatial consensus level for each, de-risking downstream exploration. Our MPM results agree qualitatively with exploration and geological knowledge. In particular, our method identified areas of high prospectivity in known exploration regions and geologically and geospatially corresponding to the known extents of both mineral systems. The convergence rate of the ensemble demonstrated a high level of statistical durability of our MPM products, suggesting that they can guide exploration at a national scale until significant new data emerge. Potential new exploration targets for PGE–Ni–Cu–Cr are located northwest of the Bushveld Complex; for Au, promising areas are west of the Witwatersrand Basin. The broader implications of this work for the mineral industry are profound. As exploration becomes more data-driven, the question of trust in MPM products must be addressed; it can be done using the proposed scientific method. Graphical Abstract

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Dry reforming of methane: Advances in coke mitigation strategies via siliceous catalyst formulations - Abdulkadir Tanimu; Basiru O. Yusuf; Saheed Lateef; Gazali Tanimu; Aliyu M. Alhassan; Musa O. Azeez; Khalid Alhooshani; Saheed A. Ganiyu (Journal of Environmental Chemical Engineering, 2024)

Self-condensation for enhancing the hydrophilicity of covalent organic polymers and photocatalytic hydrogen generation with unprecedented apparent quantum yield up to 500 nm - Islam M.A. Mekhemer; Ahmed M. Elewa; Mohamed M. Elsenety; Maha Mohamed Samy; Mohamed Gamal Mohamed; Ahmed Fouad Musa; Tse-Fu Huang; Tzu-Chien Wei; Shiao-Wei Kuo; Bo-Han Chen; Shang-Da Yang; Ho-Hsiu Chou (Chemical Engineering Journal, 2024)

Alleviation of Copper-Induced Hepatotoxicity by Bergenin: Diminution of Oxidative Stress, Inflammation, and Apoptosis via Targeting SIRT1/FOXO3a/NF-κB Axes and p38 MAPK Signaling - Samyah T. Alanazi; Samir A. Salama; Musaad M. Althobaiti; Rana A. Alotaibi; Ammar A. AlAbdullatif; Arafa Musa; Gamaleldin I. Harisa (Biological Trace Element Research, 2024)

Co-composting of Black Soldier Fly Frass (BSFF) with various organics additives for nutrient enhancement - Kai Tong Woo; Rashid Shamsuddin; Mohd Hakimi; M. Devendran Manogaran; Lee Wen Looi; Ze Sen Tan; Abdulhalim Musa Abubakar (Bioresource Technology Reports, 2024)

Ethnobotany of Food Plants Used in the Kimvula Territory (Kongo Central Province) in Congo, DR [Ethnobotany of Foods Plants in Congo, DR] - Lemmy K. Lassa; Guy B. Ilumbe; Jean-Paul Koto-Te-Nyiwa Ngbolua; Apollinaire M. Biloso; Da Musa Y. Masens; Jean-Pierre M. Habari; Félicien L. Lukoki (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Ecotourism and mangrove conservation in Southeast Asia: Current trends and perspectives - Austin Blanton; Ewane Basil Ewane; Freddie McTavish; Michael S. Watt; Kerrylee Rogers; Redeat Daneil; Irene Vizcaino; Ana Novo Gomez; Pavithra S. Pitumpe Arachchige; Shalini A.L. King; G.A. Pabodha Galgamuwa; Martha Lucia Palacios Peñaranda; et al. (Journal of Environmental Management, 2024)

Monitoring the ionospheric conditions during the annular solar eclipse December 2019: A case study - Siti Syukriah Khamdan; Tajul Ariffin Musa; Suhaila M. Buhari; Kornayat Hozumi; Neil Ashcroft; Nashriq Ferdaus Ahmad; Clara Yatini (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

A global assessment of environmental and climate influences on wetland macroinvertebrate community structure and function - Luis B. Epele; Emilio A. Williams‐Subiza; Matthew S. Bird; Aurelie Boissezon; Dani Boix; Eliane Demierre; Conor G. Fair; Patricia E. García; Stephanie Gascón; Marta G. Grech; Hamish S. Greig; Michael Jeffries; et al. (Global Change Biology, 2024)
Estimating organisms' responses to environmental variables and taxon associations across broad spatial scales is vital for predicting their responses to climate change. Macroinvertebrates play a major role in wetland processes, but studies simultaneously exploring both community structure and community trait responses to environmental gradients are still lacking. We compiled a global dataset (six continents) from 756 depressional wetlands, including the occurrence of 96 macroinvertebrate families, their phylogenetic tree, and 19 biological traits. Using Bayesian hierarchical joint species distribution models (JSDMs), we estimated macroinvertebrate associations and compared the influences of local and climatic predictors on both individual macroinvertebrate families and their traits. While macroinvertebrate families were mainly related to broad‐scale factors (maximum temperature and precipitation seasonality), macroinvertebrate traits were strongly related to local wetland hydroperiod. Interestingly, macroinvertebrate families and traits both showed positive and negative associations to the same environmental variables. As expected, many macroinvertebrate family occurrences were positively associated with temperature, but a few showed the opposite pattern and were found in cooler or montane regions. We also found that wetland macroinvertebrate communities would likely be affected by changing climates through alterations in traits related to precipitation seasonality, temperature seasonality, and wetland area. Temperature increases may negatively affect collector and shredder functional groups. A decrease in precipitation could lead to reductions in wetland area benefiting drought‐tolerant macroinvertebrates, but it may negatively affect macroinvertebrates lacking those adaptations. Wetland processes may be compromised through broad‐scale environmental changes altering macroinvertebrate family distributions and local hydroperiod shifts altering organism traits. Our complementary family‐based and trait‐based approaches elucidate the complex effects that climate change may produce on wetland ecosystems.

Added value upshot of barley amalgamation in wheat flour to boost the physico-chemical quality attributes of flat bread - Muhammad Abdullah; Muhammad Zulkiffal; Tabussam Tufail; Farah Naz Akbar; Muhammad Owais; Javed Ahmed; Ahsan Javed; Muhammad Ijaz Tabassum; Amna Kanwal; Muhammad Asghar; Muhammad Musa; M. A. Rehman Arif; et al. (Cereal Research Communications, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Food safety policy enforcement and associated actions reduce lead chromate adulteration in turmeric across Bangladesh - Jenna E. Forsyth; Musa Baker; Syeda Nurunnahar; Shariful Islam; M. Saiful Islam; Tauhidul Islam; Erica Plambeck; Peter J. Winch; Dinsha Mistree; Stephen P. Luby; Mahbubur Rahman (Environmental Research, 2023)

Reviewing biohydrogen production from microalgal cells through fundamental mechanisms, enzymes and factors that engendering new challenges and prospects - Jia Min Woon; Kuan Shiong Khoo; Mehdi Akermi; Meznah M. Alanazi; Jun Wei Lim; Yi Jing Chan; Pei Sean Goh; Boredi Silas Chidi; Man Kee Lam; Juliana Zaini; Muhammad Roil Bilad; Yuguang Zhou; et al. (Fuel, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Calcareous nannofossil biostratigraphy and bioevents across the Ypresian/Lutetian boundary in Egypt and Jordan - Ikhlas Alhejoj; M. Faris; F. Ahmad; S. Farouk; J. Sreepat; G. Musa; M. Shama (Journal of African Earth Sciences, 2023)

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

Tropical sharks feasting on and swimming through microplastics: First evidence from Malaysia - Daniel M. Matupang; Haziq I. Zulkifli; Jonathan Arnold; Azwan Mat Lazim; Mazlan Abd. Ghaffar; Syafiq M. Musa (Marine Pollution Bulletin, 2023)

Performance of the local ionospheric model in resolving GPS baseline ambiguity over the Malaysian region - Siti Syukriah Khamdan; Tajul Ariffin Musa; Suhaila M. Buhari; Abdullah Hisam Omar (GPS Solutions, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Facilitation of dependent transfers with functional neuromuscular stimulation: a computer simulation study - Nicholas F. Bean; Lisa M. Lombardo; Ronald J. Triolo; Musa L. Audu (Medical & Biological Engineering & Computing, 2022)

Ecofriendly adsorption and sensitive detection of Hg (II) by biomass-derived nitrogen-doped carbon dots: process modelling using central composite design - Mohammed Abdullah Issa; Hamid Zentou; Zaid H. Jabbar; Zurina Z. Abidin; Haninah Harun; Noor Amirah Abdul Halim; Mohammed M. Alkhabet; Musa Y. Pudza (Environmental Science and Pollution Research, 2022)

RACE-SM: Reliability and adaptive cooperation for efficient UWSNs using sink mobility - Irfan Ahmad; Taj Rahman; Inayat Khan; Salman Jan; Shahrulniza Musa; M. Irfan Uddin (Frontiers in Marine Science, 2022)
Underwater Wireless Sensor Networks (UWSNs) are the most crucial method for exploring the hidden resources under the water. It enables many underwater applications, such as military, commercial, disaster prevention, ocean sampling, and other emergencies. Data transmission through a single relay node creates a hotspot, which will minimize the network lifetime and reduce the network reliability. Therefore, the cooperative technique is essential for transferring data between the source and the destination. This research proposes an improved version of Reliability and Adaptive Cooperation for Efficient (RACE), a well-known cooperative routing protocol for UWSNs known as RACE-SM. RACE-SM solved the single relay node issues by using the sink mobility scheme. All sensor nodes transfer data directly to the sink node if the sink node is in the communication range. Otherwise, sensor nodes use the cooperative combining strategies scheme to send the data from the source to the destination or sink node. The performance of the proposed method is then compared with the current protocols. The simulation results show that the RACE-SM outperforms in average up to 40.60%, 59%, 278%, and 77% than current protocols in terms of alive nodes, energy consumption, packet delivery ratio (PDR), and end-to-end delay respectively.

A new diterpene and other constituents of Salvia multicaulis from Jordan - Lina M. Barhoumi; Hala I. Al-Jaber; Musa H. Abu Zarga (Natural Product Research, 2022)

Prediction of compressive strength of concrete incorporated with jujube seed as partial replacement of coarse aggregate: a feasibility of Hammerstein–Wiener model versus support vector machine - Musa Adamu; S. I. Haruna; Salim Idris Malami; M. N. Ibrahim; S. I. Abba; Yasser E. Ibrahim (Modeling Earth Systems and Environment, 2022)

Implementation of soft-computing models for prediction of flexural strength of pervious concrete hybridized with rice husk ash and calcium carbide waste - Salim Idris Malami; A. A. Musa; S. I. Haruna; U. U. Aliyu; A. G. Usman; M. I. Abdurrahman; Abba Bashir; S. I. Abba (Modeling Earth Systems and Environment, 2022)

Pest activity and natural enemy diversity in stored dry date (Phoenix dactylifera L. (Arecales: Arecaceae)) in the Northern Guinea Savannah Agroecological Zone - D. M. Mailafiya; L. J. Bamaiyi; B. T. Magaji; I. P. Musa; A. J. Kwanashie; O. O. Banwo; L. Y. Bawa (International Journal of Tropical Insect Science, 2022)

Occupational rhinitis and asthma in bakers: a cross-sectional study in the former Katanga province of DR Congo - Joseph Pyana Kitenge; Paul Musa Obadia; Trésor Carsi Kuhangana; Tony Kayembe-Kitenge; Patient Nkulu Banza; Lilian Nsenga Mukanda; Pascal Nawej Tshimwang; Patrick D. M. C. Katoto; Celestin Banza Nkulu Lubaba; Abdon Mukalay wa Mukalay; Benoit Nemery (International Archives of Occupational and Environmental Health, 2022)

Multilocus phylogenetics of smooth clam shrimps (Branchiopoda, Laevicaudata) - Zandra M. S. Sigvardt; Jørgen Olesen; D. Christopher Rogers; Brian Timms; Musa Mlambo; Nicolas Rabet; Ferran Palero (Zoologica Scripta, 2021)
Laevicaudatan branchiopods, also called ‘smooth clam shrimps’ or ’pea shrimps’, are rare crustaceans found exclusively in temporary, small freshwater bodies, which stay dry most of the year. Only 42 laevicaudatan species have been described so far, 90% of which belong to the genus Lynceus . The first multilocus phylogeny of the group is provided here, based on 15 Lynceus species from North and South America, Europe, Africa, Asia, Australia and New Caledonia and using nine molecular markers (two mitochondrial and seven nuclear genes, including newly designed primers). Genetic data suggest populations of Lynceus brachyurus from Europe and North America to represent a complex of cryptic species and sister group to all other laevicaudatans. Species from Thailand, Japan, Mongolia and China formed a distinct East Asian clade. A Southern Hemisphere (Gondwanaland) clade, composed of Chilean, Australian and New Caledonian taxa, was found weakly clustering with an African Lynceus species. Relaxed molecular clock analyses indicate a Pangean origin of Laevicaudata, with further diversification due to vicariance and the continued splitting of continents. Rostrum characters, which are particularly relevant for laevicaudatan systematics, were re‐evaluated and provide morphological evidence supporting molecular clades. Our worldwide overview of Laevicaudata evolution highlights that recent sampling from Africa and South America is scarce, and that further DNA efforts should focus on Paralimnetis and Lynceiopsis species.

Relationship of irrigated wheat yield with temperature in hot environments of Sudan - Abuelgasim I. I. Musa; Mitsuru Tsubo; Imad-Eldin A. Ali-Babiker; Toshichika Iizumi; Yasunori Kurosaki; Yasuomi Ibaraki; Faisal M. A. El-Hag; Izzat S. A. Tahir; Hisashi Tsujimoto (Theoretical and Applied Climatology, 2021)
A negative effect of increasing temperature on wheat production in the coming decades has been projected for Sudan, which is a major wheat producer in Sub-Saharan Africa. Wheat is susceptible to high temperature, so trend analysis of historical yields together with observed temperature is critical for understanding the effect of climate change. The objective of this study was to determine the association between yield of irrigated wheat in hot drylands of Sudan and temperature during the growing season (November–February). Regional-scale yield data in three major wheat-producing areas (Northern State, Gezira State, and Kassala State) in 48 crop seasons (1970/71–2017/18) were used to determine the correlation of yield with maximum (TMAX) and minimum temperatures (TMIN) at representative meteorological stations (Dongola, Wad Medani, and New Halfa, respectively). Frequencies of days with maximum temperature above 35 °C (THD) and minimum temperature above 20 °C (THN) were also used for correlation analysis. In all three areas, regression analysis detected upward trends in the growing-season temperature. The increase in temperature was particularly evident at Dongola, although no such trend has been reported previously. The yields were negatively correlated with the growing-season temperature, particularly THN in Northern State, TMAX in Gezira State, and TMIN in Kassala State. These results confirm that the recent increase in the growing-season temperature might have reduced the yield to some extent in the breadbasket of Sudan.

Integrated Water Harvesting and Aquifer Recharge Evaluation Methodology Based on Remote Sensing and Geographical Information System: Case Study in Iraq - Muthanna M. A. AL-Shammari; Ayser M. AL-Shamma’a; Ali Al Maliki; Hussain Musa Hussain; Zaher Mundher Yaseen; Asaad M. Armanuos (Natural Resources Research, 2021)

Contrasting Neoproterozoic and Mesozoic granitoids in Zaranda complex (Nigeria): insights into the distinct origins, tectonic settings and mineralization potential - Hafizullah Abba Ahmed; Lian-Xun Wang; Chang-Qian Ma; Mohammed I. M. Abdallsamed; Musa Bala Girei; Yu-Xiang Zhu; Victor Ikechukwu Vincent; Dlama Vandi Kamaunji; Liang Cao (International Journal of Earth Sciences, 2021)

The role of anthropogenic habitats in freshwater mussel conservation - Ronaldo Sousa; Dariusz Halabowski; Anna M. Labecka; Karel Douda; Olga Aksenova; Yulia Bespalaya; Ivan Bolotov; Juergen Geist; Hugh A. Jones; Ekaterina Konopleva; Michael W. Klunzinger; Carlos A. Lasso; et al. (Global Change Biology, 2021)
Anthropogenic freshwater habitats may provide undervalued prospects for long‐term conservation as part of species conservation planning. This fundamental, but overlooked, issue requires attention considering the pace that humans have been altering natural freshwater ecosystems and the accelerated levels of biodiversity decline in recent decades. We compiled 709 records of freshwater mussels (Bivalvia, Unionida) inhabiting a broad variety of anthropogenic habitat types (from small ponds to large reservoirs and canals) and reviewed their importance as refuges for this faunal group. Most records came from Europe and North America, with a clear dominance of canals and reservoirs. The dataset covered 228 species, including 34 threatened species on the IUCN Red List. We discuss the conservation importance and provide guidance on how these anthropogenic habitats could be managed to provide optimal conservation value to freshwater mussels. This review also shows that some of these habitats may function as ecological traps owing to conflicting management practices or because they act as a sink for some populations. Therefore, anthropogenic habitats should not be seen as a panacea to resolve conservation problems. More information is necessary to better understand the trade‐offs between human use and the conservation of freshwater mussels (and other biota) within anthropogenic habitats, given the low number of quantitative studies and the strong biogeographic knowledge bias that persists.

Senna reticulata: a Viable Option for Bioenergy Production in the Amazonian Region - Adriana Grandis; Bruna C. Arenque-Musa; Marina C. M. Martins; Thais Olivar Maciel; Rachael Simister; Leonardo D. Gómez; Marcos S. Buckeridge (BioEnergy Research, 2021)

The Influence of Ramp Shape Parameters on Performance of Overtopping Breakwater for Energy Conversion - M. A. Musa; M. F. Roslan; M. F. Ahmad; A. M. Muzathik; M. A. Mustapa; A. Fitriadhy; M. H. Mohd; M. A. A. Rahman (Journal of Marine Science and Engineering, 2020)
Overtopping breakwater for energy conversion (OBREC) is integration between breakwater and wave energy converter (WEC) that allows incoming waves to be stored in the reservoir. The higher the overtopping amount collected in a reservoir, the greater the energy generated will be. Hence, most of the overtopping concept has attempted to maximize the inclusion of water in the reservoir by optimizing geometrical parameters, particularly the ramp angle. However, the studies corresponding to ramp shapes geometries have not been adequately reviewed. Most studies only focused on the usage of linear overtopping ramp shape. There is still limited knowledge on the influence of different ramp shape parameters towards the overtopping wave. Thus, this paper aimed to push the border of available knowledge by investigating the influence of the ramp shape parameters to the overtopping wave discharge through simulation and experimenting approaches. Seven different ramp shapes have been tested under Malaysia’s wave condition and a new ramp shape parameter allowing for maximized overtopping wave on OBREC is presented.

Chemical constituents of the aerial parts of Salvia judaica Boiss. from Jordan - Mahmoud A. Al-Qudah; Hasan I. Tashtoush; Ethar F. Khlaifat; Sahar O. Ibrahim; Ayman M. Saleh; Hala I. Al-Jaber; Musa H. Abu Zarga; Sultan T. Abu Orabi (Natural Product Research, 2020)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Effect of hemoglobin polymorphism on performance traits in indigenous chicken genotypes in Nigeria - M. Orunmuyi; H. Muhammad; A. A. Musa; A. K. Olutunmogun; B. I. Nwagu (Tropical Animal Health and Production, 2020)

A molecular prevalence survey on Anaplasma infection among domestic ruminants in Khartoum State, Sudan - Nagwa M. Eisawi; Abdel Rahim M. El Hussein; Dina A. Hassan; Azza B. Musa; Mohammed O. Hussien; Khalid A. Enan; Mohammed A. Bakheit (Tropical Animal Health and Production, 2020)

Ocean warming and hypoxia affect embryonic growth , fitness and survival of small‐spotted catsharks , Scyliorhinus canicula - Syafiq M. Musa; Daniel M. Ripley; Timo Moritz; Holly A. Shiels (Journal of Fish Biology, 2020)
Elasmobranchs are key to a healthy marine ecosystem but are under threat from human activities, such as destructive fisheries and shark finning. Embryos of oviparous elasmobranchs may be further challenged during development by rising temperatures and falling dissolved oxygen concentrations in their intertidal environment. However, the impact of climate change on survival and growth of oviparous elasmobranchs is still poorly understood. Here, we investigate the effects of temperature and hypoxia on the growth and survival of small‐spotted catshark ( Scyliorhinus canicula ) embryos by incubating eggs in normoxia 15°C, normoxia 20°C, hypoxia 15°C, or hypoxia 20°C. Incubation under the elevated temperature increased the embryonic growth rate, yolk consumption rate and Fulton's condition factor at hatching, whilst decreasing the total length and body mass of newly hatched sharks. Under low oxygen conditions (50% air saturation) the survival rate of S. canicula embryos dropped significantly and the temperature‐induced increase in Fulton's condition factor was reversed. Together, these data demonstrate both the individual and compound effects of elevated temperature and hypoxia on the survival and growth during early ontogeny of a ubiquitous, coastal elasmobranch, S. canicula .

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Chemical constituents of Fumaria densiflora and the effects of some isolated spirobenzylisoquinoline alkaloids on murine isolated ileum and perfused heart - Adel M. Al-Ghazzawi; Musa H. Abu Zarga; Shtaywy S. Abdalla (Natural Product Research, 2020)

Healthcare Economics of Hydrocephalus After Aneurysmal Subarachnoid Hemorrhage in the United States - Syed M. Adil; Beiyu Liu; Lefko T. Charalambous; Musa Kiyani; Robert Gramer; Christa B. Swisher; Laura Zitella Verbick; Aaron McCabe; Beth A. Parente; Promila Pagadala; Shivanand P. Lad (Translational Stroke Research, 2019)

Street dust heavy metal pollution implication on human health in Nicosia, North Cyprus - A A Musa; S M Hamza; R Kidak (Environmental Science and Pollution Research, 2019)

Exploring the demarcation requirements of fish breeding and nursery sites to balance the exploitation, management and conservation needs of Lake Victoria ecosystem - Christopher Mulanda Aura; Chrisphine Sangara Nyamweya; James M. Njiru; Safina Musa; Zachary Ogari; Linda May; Enock Wakwabi (Fisheries Management and Ecology, 2019)
Fisheries resources in vital freshwater ecosystems have been reported to be under immense threat, resulting in conflicts between conservation, management and exploitation. This study established requirements for identifying and mapping fish breeding and nursery grounds in such ecosystems in the Kenyan part of Lake Victoria. The criteria were characterised by the use of indigenous knowledge, field data, literature on breeding sites, macroinvertebrates distribution, larval and relative fish abundances, digitisation, participatory mapping, and periodic sampling. Data were collected from trawl and seine net surveys. Digitisation and mapping of the proposed conservation sites were carried out using Quantum GIS software. Participatory physical demarcation of sites was done using buoys and markers. Larval and juvenile fishes were diverse and abundant in all seven river mouths and six bays surveyed with little variance; an important aspect of breeding areas. Additionally, a preponderance of macroinvertebrates and high fish diversity compared with offshore sites in the lake strengthened the hypothesis that these are critical habitats for spawning and preferred habitats for nurseries for fish. The approach can be adopted globally to guarantee the long‐term integrity of critical fish habitats for sustainable fisheries management and blue growth.

Mycotoxins in poultry feed and feed ingredients in Nigeria - Oyekemi O. Akinmusire; Abdul-Dahiru El-Yuguda; Jasini A. Musa; Oluwawapelumi A. Oyedele; Michael Sulyok; Yinka M. Somorin; Chibundu N. Ezekiel; Rudolf Krska (Mycotoxin Research, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Using fish landing sites and markets information towards quantification of the blue economy to enhance fisheries management - Christopher Mulanda Aura; Chrisphine S. Nyamweya; James M. Njiru; Cyprian Odoli; Safina Musa; Zachary Ogari; Richard Abila; Raphael Okeyo; Robert Oketch (Fisheries Management and Ecology, 2019)
Fisheries management uses important fish market information and information from Communication Technology ( ICT ) to improve fish trade by identifying inefficiencies, inequity and post‐harvest losses. The current study reports fisheries output using ICT at major landing sites and markets in Kenya and Uganda from the Kenya Marine and Fisheries Research Institute ( KMFRI ) Enhanced Fish Market Information Service ( EFMIS ) database for 2009 – 2017. Catch assessment survey data validated the use of market data in drawing conclusions. Regional Frame Survey data provided information before EFMIS , enabling comparisons of fish trade costings. The average quantity of fish traded in Kenya depended on seasons of active lake fishing, which occurs in January – March and August – October, while Uganda had an irregular pattern associated with fish trade throughout the year. The quantity of fish traded weekly depended on the average price of fish. Lower sales margins during the EFMIS project showed the merits of information sharing using ICT platforms for efficient and equitable fish trade. Such evaluation of fish market information is useful in fish trade policy formulation and for fisheries management and ecological sustainability in rural and peri‐urban communities.

Deeper knowledge of shallow waters: reviewing the invertebrate fauna of southern African temporary wetlands - Matthew S. Bird; Musa C. Mlambo; Ryan J. Wasserman; Tatenda Dalu; Alexandra J. Holland; Jenny A. Day; Martin H. Villet; David T. Bilton; Helen M. Barber-James; Luc Brendonck (Hydrobiologia, 2019)

The effects of repetitive stress on tat protein-induced pro-inflammatory cytokine release and steroid receptor expression in the hippocampus of rats - Khayelihle B. Makhathini; Oualid Abboussi; Musa V. Mabandla; William M. U. Daniels (Metabolic Brain Disease, 2018)

Poly-N-methylated Aβ-Peptide C-Terminal fragments (MEPTIDES) reverse the deleterious effects of amyloid-β in rats - Siya G. Sibiya; Musa V. Mbandla; Thavi Govender; Adeola Shobo; William M. U. Daniels (Metabolic Brain Disease, 2018)

Differential epigenetic changes in the hippocampus and prefrontal cortex of female mice that had free access to cocaine - Duyilemi C. Ajonijebu; Oualid Abboussi; Musa V. Mabandla; William M. U. Daniels (Metabolic Brain Disease, 2018)

Control of standing balance at leaning postures with functional neuromuscular stimulation following spinal cord injury - Musa L. Audu; Brooke M. Odle; Ronald J. Triolo (Medical & Biological Engineering & Computing, 2018)

New flavonol glycoside from Scabiosa prolifera L. aerial parts with in vitro antioxidant and cytotoxic activities - Mahmoud A. Al-Qudah; Noor K. Otoom; Hala I. Al-Jaber; Ayman M. Saleh; Musa H. Abu Zarga; Fatma U. Afifi; Sultan T. Abu Orabi (Natural Product Research, 2017)

Domestic water demand challenges in Qatar - Husam Musa Baalousha; Omar K. M. Ouda (Arabian Journal of Geosciences, 2017)

Critical success factors for public housing projects in developing countries: a case study of Nigeria - Musa M. Mukhtar; Roslan Bin Amirudin; Trevor Sofield; Ismail Bin Mohamad (Environment, Development and Sustainability, 2017)

Current knowledge of metabolomic approach in infectious fish disease studies - C‐F Low; M Z H Rozaini; N Musa; B Syarul Nataqain (Journal of Fish Diseases, 2017)
The approaches of transcriptomic and proteomic have been widely used to study host–pathogen interactions in fish diseases, and this is comparable to the recently emerging application of metabolomic in elucidating disease‐resistant mechanisms in fish that gives new insight into potential therapeutic strategies to improve fish health. Metabolomic is defined as the large‐scale study of all metabolites within an organism and represents the frontline in the ‘omics’ approaches, providing direct information on the metabolic responses and perturbations in metabolic pathways. In this review, the current research in infectious fish diseases using metabolomic approach will be summarized. The metabolomic approach in economically important fish infected with viruses, bacteria and nematodes will also be discussed. The potential of the metabolomic approach for management of these infectious diseases as well as the challenges and the limitations of metabolomic in fish disease studies will be explored. Current review highlights the impacts of metabolomic studies in infectious fish diseases, which proposed the potential of new therapeutic strategies to enhance disease resistance in fish.

Anti-proliferative study and isolation of Ochnaflavone from the ethyl acetate-soluble fraction of Ochna kibbiensis Hutch & Dalziel - Abdullahi M. Ismail; Aliyu M. Musa; Tajuddeen Nasir; Mohammed G. Magaji; Yusuf A. Jega; Iliya Ibrahim (Natural Product Research, 2017)

Serological survey for Brucella antibodies in donkeys of north-eastern Nigeria - A. O. Tijjani; A. U. Junaidu; M. D. Salihu; A. A. Farouq; O. O. Faleke; S. G. Adamu; H. I. Musa; I. U. Hambali (Tropical Animal Health and Production, 2017)

Mutagenicity assessment of aerosols in emissions from domestic combustion processes - Nuno Canha; Isabel Lopes; Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Susana Marta Almeida; Célia A. Alves (Environmental Science and Pollution Research, 2017)

Nitrite in processed meat products in Khartoum, Sudan and dietary intake - Aziza Hussein Bakheit Adam; Nazik Eltayeb Musa Mustafa; Ivonne M. C. M. Rietjens (Food Additives & Contaminants Part B-Surveillance, 2017)

Particulate phase emission of parent polycyclic aromatic hydrocarbons (PAHs) and their derivatives (alkyl-PAHs, oxygenated-PAHs, azaarenes and nitrated PAHs) from manually and automatically fired combustion appliances - Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Célia A. Alves (Air Quality, Atmosphere & Health, 2016)

Mutagenicity assessment of aerosols in emissions from domestic combustion processes - Nuno Canha; Isabel Lopes; Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Susana Marta Almeida; Célia A. Alves (Environmental Science and Pollution Research, 2016)

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)

Amelioration of l-Dopa-Associated Dyskinesias with Triterpenoic Acid in a Parkinsonian Rat Model - Babongile C. Ndlovu; Willie M. U. Daniels; Musa V. Mabandla (Neurotoxicity Research, 2016)

The interaction between stress and exercise, and its impact on brain function - Vivienne A. Russell; Michael J. Zigmond; Jacqueline J. Dimatelis; William M. U. Daniels; Musa V. Mabandla (Metabolic Brain Disease, 2014)

The effects of prenatal methylmercury exposure on trace element and antioxidant levels in rats following 6-hydroxydopamine-induced neuronal insult - Zulfiah Mohamed Moosa; Willie M. U. Daniels; Musa V. Mabandla (Metabolic Brain Disease, 2014)

Evaluation of the antipsychotic potential of aqueous fraction of Securinega virosa root bark extract in mice - M. G. Magaji; M. Mohammed; R. A. Magaji; A. M. Musa; I. Abdu-Aguye; I. M. Hussaini (Metabolic Brain Disease, 2014)

Relative CO2/NH3 Permeabilities of Human RhAG, RhBG and RhCG - R. Ryan Geyer; Mark D. Parker; Ashley M. Toye; Walter F. Boron; Raif Musa-Aziz (The Journal of Membrane Biology, 2013)

Differential localisation of BPIFA1 (SPLUNC1) and BPIFB1 (LPLUNC1) in the nasal and oral cavities of mice - Maslinda Musa; Kirsty Wilson; Le Sun; Apoorva Mulay; Lynne Bingle; Helen M. Marriott; Elizabeth E. LeClair; Colin D. Bingle (Cell and Tissue Research, 2012)

Exposure to prenatal stress enhances the development of seizures in young rats - Lihle Qulu; Willie M. U. Daniels; Musa V. Mabandla (Metabolic Brain Disease, 2012)

The effects of vasopressin and oxytocin on methamphetamine–induced place preference behaviour in rats - Cassandra O. Subiah; Musa V. Mabandla; Alisa Phulukdaree; Anil A. Chuturgoon; Willie M. U. Daniels (Metabolic Brain Disease, 2012)

Chemical constituents of Jordanian propolis - Safa A. Shaheen; Musa H. Abu Zarga; Ibrahim K. Nazer; Rula M. Darwish; Hala I. Al-Jaber (Natural Product Research, 2011)

Production of hyperthermostable GH10 xylanase Xyl10B from Thermotoga maritima in transplastomic plants enables complete hydrolysis of methylglucuronoxylan to fermentable sugars for biofuel production - Jae Yoon Kim; Musa Kavas; Walid M. Fouad; Guang Nong; James F. Preston; Fredy Altpeter (Plant Molecular Biology, 2011)

The catalase gene differentiates between some strains of Staphylococcus aureus ssp. anaerobius - N. O. Musa; K. Eltom; F. Gessler; H. Böhnel; A. Babiker; S. M. El Sanousi (Folia Microbiologica, 2010)

Expression and Characterization of Penicillin-Binding Proteins in Burkholderia cenocepacia - Kimberly Musa Specht; Kyle H. Sheetz; Courtney M. Alexander; Lilian T. Lamech; Lauren H. O’Connor; Dawn M. Walker; Hilary P. Stevenson (Current Microbiology, 2010)

Effect of exercise on dopamine neuron survival in prenatally stressed rats - Musa V. Mabandla; Lauriston A. Kellaway; William M. U. Daniels; Vivienne A. Russell (Metabolic Brain Disease, 2009)

The effect of electromagnetic radiation in the mobile phone range on the behaviour of the rat - Willie M. U. Daniels; Ianthe L. Pitout; Thomas J. O. Afullo; Musa V. Mabandla (Metabolic Brain Disease, 2009)

Development of a mild prenatal stress rat model to study long term effects on neural function and survival - Musa V. Mabandla; Bryony Dobson; Shula Johnson; Laurie A. Kellaway; Willie M. U. Daniels; Vivienne A. Russell (Metabolic Brain Disease, 2008)

Phytohormone levels in germinating seeds of Zea mays L. exposed to selenium and aflatoxines - Güleray Ağar; Musa Türker; Peyami Battal; M. Emre Erez (Ecotoxicology, 2006)

Bordetella avium Infection in Chickens and Quail in Nigeria: Preliminary Investigations - M. O. Odugbo; U. Musa; S. O. Ekundayo; P. A. Okewole; J. Esilonu (Veterinary Research Communications, 2006)

Signaling Pathways in the Biphasic Effect of ANG II on Na+/H+ Exchanger in T84 Cells - R. Musa-Aziz; M. Oliveira-Souza; M. Mello-Aires (The Journal of Membrane Biology, 2005)

Evaluation of sugarcane varieties for maturity earliness and selection for efficient sugar accumulation - M. E. Wagih; A. Ala; Y. Musa (Sugar Tech, 2004)

Fundamental botanical and agronomical characterisation of sugarcane cultivars for clonal identification and monitoring genetic variations - M. E. Wagih; Y. Musa; A. Ala (Sugar Tech, 2004)

Determination of Exposure to Polycyclic Aromatic Hydrocarbons in Some Work Groups in Turkey by Measurement of 1-Hydroxypyrene Levels in Urine - İ. Ateş; M. Yılmazer-Musa; B. Yücesoy; A. Karakaya (Bulletin of Environmental Contamination and Toxicology, 2004)

Regeneration and evaluation of sugarcane somaclonal variants for drought tolerance - M. E. Wagih; A. Ala; Y. Musa (Sugar Tech, 2004)

biomass analysis and selection of sugarcane genotypes for drought tolerance - M. E. Wagih; A. Ala; Y. Musa (Sugar Tech, 2003)

Microtubule assembly in cultured myoblasts and myotubes following nocodazole induced microtubule depolymerisation - H. Musa; C. Orton; E.E. Morrison; M. Peckham (Journal of Muscle Research and Cell Motility, 2003)